2023
DOI: 10.1093/icvts/ivad032
|View full text |Cite
|
Sign up to set email alerts
|

Surgical cytoreduction and hyperthermic intrathoracic chemotherapy for thymic tumours with pleural spread is effective on survival: results from the multicentre German hyperthermic intrathoracic chemotherapy study

Abstract: Objectives Cytoreductive surgery and hyperthermic intrathoracic chemotherapy (HITOC) is effective on survival for patients with pleural metastatic thymic tumours. Methods Multicentre, retrospective analysis of patients with stage IVa thymic tumours treated with surgical resection and HITOC. Primary end-point was overall survival, secondary end-points were recurrence-/progression-free survival and morbidity/mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The main finding of our study was a prolonged survival in selected patients with secondary pleural metastases after CRS+HITOC as a part of multimodal treatment approach with median overall survival of 39 months and median RFS/PFS of 14 months. Retrospective studies showed an encouraging survival of patients with pleural mesothelioma or thymus tumours with pleural involvement, who underwent a multimodal treatment approach including local interventions with CRS+HITOC ( 5 , 11 , 20 ). However, there is paucity of studies investigating the outcome of CRS+HITOC in patients with secondary pleural metastases as a part of multimodal concept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main finding of our study was a prolonged survival in selected patients with secondary pleural metastases after CRS+HITOC as a part of multimodal treatment approach with median overall survival of 39 months and median RFS/PFS of 14 months. Retrospective studies showed an encouraging survival of patients with pleural mesothelioma or thymus tumours with pleural involvement, who underwent a multimodal treatment approach including local interventions with CRS+HITOC ( 5 , 11 , 20 ). However, there is paucity of studies investigating the outcome of CRS+HITOC in patients with secondary pleural metastases as a part of multimodal concept.…”
Section: Discussionmentioning
confidence: 99%
“…Four high-volume departments of thoracic surgery in Germany collected data in the “German HITOC-Study” funded by the Deutsche Forschungsgemeinschaft – DFG, German Research Association (DFG, RI2905/3-1). The study group has already published first results about HITOC after CRS for pleural malignancies in general and for thymic tumours with pleural spread ( 5 , 13 , 14 ). Now, the focus will be on secondary pleural metastases and its surgical treatment combined with HITOC.…”
Section: Methodsmentioning
confidence: 99%
“…Evidently, the data presented by the multicentre German group are significant, but confirmation by others authors is demanded. To reinforce the data obtained by Ried et al [ 2 ], Chappuy et al [ 10 ] reported an important experience with 40 patients with T IVa pleural involvement treated with partial pleurectomy and HITHOC showing a median length of survival of 118 months and a median DFI of 70 months [ 10 ]. The group of Pisa in Italy had also similar results [ 11 ].…”
mentioning
confidence: 85%
“…The answer to this question could be found in the good results reported from the multicentre German HITOC study entitled ‘Surgical cytoreduction and hyperthermic intrathoracic chemotherapy for thymic tumours with pleural spread is effective on survival: results from the multicentre German HITOC-study’ [ 2 ]. The study includes 42 patients with T and 15 patients with TC with pleural metastases or recurrences.…”
mentioning
confidence: 99%
See 1 more Smart Citation